ANALYSIS OF TOTAL FLAVANOID LEVELS OF FENNEL LEAVES (FOENICULUM VULGARE) ETHANOL EXTRACT BY SPECTROPHOTOMETRY VISIBEL - Alifia Ni’ma; Novena Yety Lindawati (Universitas Muhammadiyah Magelang, 2022)
Flavonoid is the compounds in nature that play a role in increasing body immunity. Flavonoids in green plants can be sourced from fennel leaves. The aims of the study were to determine the total levels of flavonoids in fennel leaves (Foeniculum vulgare) using Visible Spectrophotometry. Maceration extracted samples using ethanol 96% solvent. Qualitative analysis of flavonoids using dilute NaOH, Wilstater-cyanidin method, and AlCl3. Quersetin used as standard solution. Quantitative analysis was carried out by colorimetric method with ALCl3 reagent as a complex compound. Quantitative analysis was continued with Visible Spectrophotometry on operating time at the 28th minute and a wavelength of 430.5 nm. Qualitative analysis indicate that the ethanol extract of fennel leaves was positive flavonoids. The total flavonoid content of fennel leaves ethanol extract was 99.2 mg QE/g extract with a coefficient of variation 1.27%.